Formulation development and evaluation of oil-based PLGA nanocarriers of fluticasone propionate - Shejwal, Aniruddha; Shevalkar, Ganesh B.; Borse, Laxmikant B. (Journal of Applied Pharmaceutical Research, 2025)
Background: Fluticasone Propionate (FP), a potent corticosteroid, suffers from poor aqueous solubility and limited skin permeability, which reduces its clinical efficacy in topical applications. This work aims to overcome these limitations; oil-based poly(lactic-co-glycolic acid) (PLGA) nanocarriers were developed to enhance the solubility, stability, and sustained release of FP. Methodology: A 3² factorial design was employed to formulate nine batches of PLGA nanocarriers loaded with FP using varying concentrations of PLGA and Capmul MCM. The formulations were evaluated for particle size, zeta potential, drug content, and in vitro drug release. The optimized batch was further characterized using Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC), and X-Ray Diffraction (XRD). Stability studies were conducted over 30 days under accelerated conditions. Results and Discussion: Among all batches, formulation F1 exhibited optimal characteristics, with a particle size of 197.5 nm, a zeta potential of -27.4 mV, and a drug content of 99.85%. The in vitro drug release profile showed a sustained release of 97% over 12 hours. SEM confirmed a spherical morphology with uniform distribution, while DSC and XRD analyses indicated the amorphous dispersion of the drug within the PLGA matrix. The formulation remained physically and chemically stable during the 30-day accelerated stability testing. Conclusion: The study demonstrates that oil-based PLGA nanocarriers effectively enhance the solubility and controlled delivery of Fluticasone Propionate. Although in vivo validation is pending, the system offers promising potential for improving topical corticosteroid therapy in clinical settings. The novelty of this formulation lies in the strategic combination of Isopropyl Myristate and PLGA to create an oil-based nanocarrier platform, which has not been previously reported for Fluticasone Propionate. This approach enables superior drug encapsulation, enhanced skin permeability, and controlled drug delivery.